A Facile Chemical Precipitation Method for the Synthesis of Nd(OH)3 and La(OH)3 Nanopowders and their Supercapacitor Performances. Issue 45 (4th December 2018) - Arunachalam, Subasri; Kirubasankar, Balakrishnan; Rajagounder Nagarajan, Erumaipatty; Vellasamy, Devadoss; Angaiah, Subramania
Abstract: A facile chemical precipitation method is used to prepare both lanthanum hydroxide [La(OH)3 ] and neodymium hydroxide [Nd(OH)3 ] nanopowders in an ambient temperature without the addition of any surfactants. Both rare‐earth hydroxides nanopowders are characterized by X‐ray diffraction and FE‐SEM analysis. The supercapacitor performances of La(OH)3 and Nd(OH)3 electrodes are studied by cyclic voltammetry, electrochemical AC‐impedance and galvanostatic charge‐discharge studies. It revealed that Nd(OH)3 electrode possesses a high specific capacitance ( Csp ) than La(OH)3 electrode. Hence, an asymmetric supercapacitor device is fabricated and denoted as Nd(OH)3 ||AC in 6 M KOH as the electrolyte soaked in the electrospun poly(vinylidene fluoride) membrane as the separator, which exhibited an energy density of 18.8 Wh kg −1 at a power density of 796 W kg −1 . Abstract : Rare‐earth hydroxide electrodes: A facile chemical precipitation method is used to prepare rare‐earth hydroxide, RE(OH)3 nanopowders [RE=La and Nd]. Electrochemical performance of RE(OH)3 electrodes reveal that Nd(OH)3 electrode has higher specific capacitance than La(OH)3 electrode. Further, the fabricated Nd(OH)3 | PVdF‐6 M KOH|AC ASC device has delivered a high energy density of 18 Wh kg −1 and a power density of 793 W kg −1 .